Rislev-Fundet. Anthropologisk Redegørelse - Jørgensen, J. Balslev (Kuml, 1961)
The Rislev Find. Anthropological Statement. Skeletal parts belonging to altogether 4 individuals were found, 2 of which being represented by single fragments only, while the skeletons of the 2 others were practically complete. These were the skeletons of 2 women. One (I) quite young, aged 18-19 years, the growing zones on the bones being still present, the other (II) somewhat older, aged about 30 years, as the growing zones in the extremities were closed whereas the sutures of the skull were not fused. These 2 women present features of particular interest as both the shape of their skulls and the build of their bodies differ somewhat from what was common in the Iron Age of this country. The skulls were shorter and lower, the base of the head was flatter and the face broader than in the very uniform long-headed Iron Age folk known hitherto. The body build differed; in that the bones were, on the whole, heavier and more robust, the muscle attachment more marked, than is otherwise seen. This is so much the more remarkable as the skeletons were of women. The height can be calculated with fair certainty to have been 160 cm (5’ 3") for both women. The 2 human skeletons from Rislev belong, thus, to a race which has not been observed previously in the extensive skeletal material from the Early Iron Age in Denmark. ]. Balslev Jørgensen.